Relevance of composition and localisation of raw rice grains to texture of cooked rice - Awg Hj Tengah, Hjh Noorhasifah (2016)
Previous research has shown that the sticky behaviour of rice may be affected by the composition and structural properties of the rice starch (amylose and amylopectin) as well as the protein and lipid components. Analyses tend to have been based on whole rice grains even though the sticky texture of rice is largely a surface phenomenon; hence, it is essential to develop an understanding of the external composition of rice grains. The objective of this PhD project is to provide an analysis of the internal and external structure of raw rice grains and to investigate how these structure data correlate to the sticky behaviour of cooked rice. The results of Attenuated Total Reflectance – Fourier Transform Infrared spectroscopy show that there is a significant difference in amide and lipid peaks and order of starch between the centre of rice grains and the external regions while X-Ray Diffraction exhibit differences in starch crystallinity. Results of Fourier Transform Infrared microspectroscopy also demonstrated the non-uniformity of amide and lipid peaks across the cross-section of a rice grain. With the aid of chemical analysis, it was concluded that the sticky texture of cooked rice is negatively correlated to the external protein and lipid amount whereas the correlation to the order of starch and starch crystallinity was positive. This is further confirmed as the removal of protein and lipid from the surface of rice grains resulted in a more adhesive cooked rice texture. This project highlights the importance of a surface study when considering rice stickiness.